What Drives Millennial Eco-Travelers? Investigation of Value–Norm Theory with Destination Responsibility as Moderator - Solekah, Nihayatu Aslamatis; Rozi, M. Fatkhur; Mardiana, Mardiana (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Understanding pro-environmental behavior in sustainable tourism is crucial for aligning marketing with traveler values. This study advances the behavioral discourse by applying the Value–Identity–Personal Norm (VIP) model, examining how destination social responsibility (DSR) moderates millennial travelers’ green behavior in natural tourism. A sample of 202 millennials visiting ten ecotourism sites in Malang Raya was analyzed using SEM-PLS 3.0. Results show that altruistic and biospheric values significantly shape environmental self-identity, which in turn reinforces personal norms. Both green trust and DSR significantly influence pro-environmental behavior, while DSR strengthens the link between personal norms and eco-behavior. These findings reveal how perceived responsibility at the destination level activates moral obligations and trust, ultimately enhancing sustainable actions. Practically, tourism stakeholders must not only protect ecological value but also build visible, credible responsibility efforts—lest they risk eroding the very norms that drive millennial environmental stewardship.